2016
DOI: 10.1371/journal.pntd.0005095
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiological Characteristics and Dynamic Transmission of Dengue in China, 2013

Abstract: BackgroundThere was a dengue epidemic in several regions of China in 2013. No study has explored the dynamics of dengue transmission between different geographical locations with dengue outbreaks in China. The purpose of the study is to analyze the epidemiological characteristics and to explore the dynamic transmission of dengue in China, 2013.Methodology and Principal FindingsRecords of dengue cases of 2013 were obtained from the China Notifiable Disease Surveillance System. Full E-gene sequences of dengue vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 37 publications
(36 reference statements)
2
24
0
Order By: Relevance
“…This study reports sex‐based differences in the manifestations of DENV infection. Similar results have been reported in Mexico City,in French Caribbean islands, and in select Chinese localities . One study in Korea, a country in which DENV is almost exclusively imported by travelers, found significantly higher DENV incidence in men .…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…This study reports sex‐based differences in the manifestations of DENV infection. Similar results have been reported in Mexico City,in French Caribbean islands, and in select Chinese localities . One study in Korea, a country in which DENV is almost exclusively imported by travelers, found significantly higher DENV incidence in men .…”
Section: Discussionsupporting
confidence: 76%
“…Previous studies have described differences in dengue presentation based on sex . Nearly 56% of the participants in our study were female and these patients had a significantly higher rate of DWWS compared to men (43.1% vs 31.3%; Table ).…”
Section: Resultsmentioning
confidence: 45%
See 2 more Smart Citations
“…Yunnan Province is located in southwestern China and neighbors the southeast Asian countries, which are all dengue-endemic areas. Research indicates that imported DF from patients from Laos and Myanmar was the primary cause of the DF epidemic in Yunnan Province [17,18,19], whereas Chinese encouragement of implementing economic development policy with Southeast Asian will result in greater contacts between Yunnan and southeast Asian countries. This finding indicates that the dengue epidemic might become increasingly common in this Chinese border area.…”
Section: Discussionmentioning
confidence: 99%